Pergeseran Kedudukan Dan Tugas Penyidik Polri Dengan Perkembangan Delik-Delik Diluar KUHP - Mukhlis R (Fakultas Hukum Universitas Riau, 2013)
For Maintaining Criminal Law criminal law required materialistic Formal, which is set in the Criminal Code. Prior to the release of Criminal Law and the position of Special Duties / Authority Police Investigator is a single investigator, and investigator investigators should coordinate with the Police Investigator, whereas after the development of offense-offense out of the Criminal Code (Special Narcotics Law and Law on Corruption Eradication), Police investigator is no longer a single investigator, but can be done by the police, investigators, and BNN. BNN Domiciled in Narcotics Case Coordinator among other investigators with extraordinary powers when compared to the authority of the police investigator in the Criminal Procedure Code and Police Act. Similarly, the discharge of Law Number 31 Year 1999 Jo Law Number 20 Year 2001 on Combating Corruption, the investigation is authorized to exercise police investigator, prosecutor and investigator KPK investigators. Police investigators located under KPK investigators, as coordinator, monitoring, supervision of other investigators with extraordinary powers when compared to the appropriate authority of the police investigators and the Criminal Procedure Police Act.